Pengembangan Sistem Informasi Pencatatan Alat LAB IPA untuk Meningkatkan Efisiensi Manajemen Inventaris - Mahdalaina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study aims to develop and implement a Science Laboratory Equipment Recording Information System to enhance the efficiency of inventory management in educational institutions. The system is designed to automate the recording, tracking, and management of laboratory equipment, ensuring accurate and organized inventory data. Key features include equipment registration, real-time tracking, maintenance scheduling, usage logs, and automated reporting. By integrating barcode scanning and data management technologies, the system ensures that all laboratory equipment is accounted for, easily retrievable, and well-maintained. The research discusses the design and development phases, including technology selection, system architecture, and user interface considerations. The system is evaluated based on its impact on operational efficiency, data accuracy, and user satisfaction. The results indicate that the implementation of the Science Laboratory Equipment Recording Information System leads to significant improvements in inventory management, reducing administrative workload and enhancing equipment utilization. The paper also addresses the challenges encountered during the development and deployment of the system, along with the solutions implemented to ensure successful integration and user adoption.